Revisit the formation of destination brand personality. (July 2022) - Wang, Jingqiang; Li, Mimi; Li, Cong; Li, Dan; Lin, Guyang
Abstract: An event-related-potential technique and the S1(cue)-S2(target) paradigm was developed to explore the effect of the onsite experience on tourists' formation and extension of destination brand personality. 18 potential visitors and 16 actual visitors were selected to complete the experiment, while their response time and N400 event-related-potential component was recorded. Neurocognitive results showed potential and actual tourists induced different response time and N400 latency patterns when identifying three types of destination personality words (weakly associated, original and extended personalities words), reflecting the effect of onsite experience on destination brand personality. These findings proved the reliability and validity of the event-related potential in the research of destination personality and demonstrated the vital role of onsite experience in destination personality. Highlights: A neuroscience method was used to measure the formation of destination personality. A S1-S2 paradigm was introduced to destination personality research. Onsite experience affects the formation and extension of destination personality. The reliability and validity of neuroscience approach in tourism research was test.